Honesty, Shame, Courage: Reconsidering the Socratic Elenchus - Fiore, Giulia (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The elenchus (gr. ἔλεγχος, literally “argument of disproof”, “refutation”, “cross-examining”) is the core of the Socratic method represented by Plato in his early dialogues. This enquiring technique, employed by Socrates to question his interlocutors about the nature or definition of ethical concepts, is the object of a never-ending scholarly debate, concerning especially its primary purpose: is it a positive method, leading to knowledge, or is it rather a negative method, aiming exclusively at refuting the interlocutor’s belief? This paper, through the analysis of some key passages in Plato’s early dialogues, focuses on the structural features of the elenchus in order to understand how the elenctic refutation is developed, why Socrates chooses a dialectical method often ending in aporia, and whether the Socratic method can be considered, not merely an instrument aiming at the recognition of one’s ignorance, but primarily a positive search for knowledge.